A changing media landscape: Science, the public and the press: The case of climate change - Susanna Priest (Mètode Science Studies Journal: Annual Review)
Economic restructuring in the media industry has eliminated many professional journalists’ jobs, reductions that may have been hardest on specialized journalists reporting areas like science, technology, economics, or international affairs. This makes audiences even more dependent on new, often social, media for scientific information. The concept of «critical science literacy» is introduced as a way to capture the skills needed to navigate science news in the evolving media landscape. While these same skills were needed to make sense of science in the «old» media world as well, the contemporary shift resulting in attenuation of authoritative journalistic voices is likely to continue, demanding more from audiences. Climate change illustrates these challenges.